2020
DOI: 10.3991/ijim.v14i19.12519
|View full text |Cite
|
Sign up to set email alerts
|

Using Reminder Tools to Increase Learning Motivation: A Comparison of Mobile Devices, Email and E-learning Platforms

Abstract: Most students are not actively concerned about curriculum activity times. However, without reminders, students will miss out on learning opportunities from the course activities. Therefore, due to the use of smartphones — which are central to people's everyday lives —, this study combined apps and the curriculum to develop a course activity notification system — Mobile Secretary of Operating Systems (MSOS) —­, as a curriculum reminder tool. This tool reminds the student of the curriculum activity times anytime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These studies have shown that using the website attributes to shape positive behavior, acquire knowledge, and attempt to find information and enhance academic achievement [13,[29][30][31]. Other findings stated that using the web can stimulate learning motivation, develop literacy, improve student activity, intensify reading apprehension and learning endurance, and increase student engagement [32][33][34][35][36][37][38]. In comparison, another study found that websites reduced student social life [30].…”
Section: Web-based Animation Videomentioning
confidence: 99%
“…These studies have shown that using the website attributes to shape positive behavior, acquire knowledge, and attempt to find information and enhance academic achievement [13,[29][30][31]. Other findings stated that using the web can stimulate learning motivation, develop literacy, improve student activity, intensify reading apprehension and learning endurance, and increase student engagement [32][33][34][35][36][37][38]. In comparison, another study found that websites reduced student social life [30].…”
Section: Web-based Animation Videomentioning
confidence: 99%
“…Moreover, technology plays a role in character building for the students [59][60][61][62][63][64]; implementing technology forms students' character, including morality, discipline, tolerance, and cooperation. Besides, student character can be developed through using blended learning [65].…”
Section: Mobile Web-based Character-building Impact On Student Charactermentioning
confidence: 99%
“…E-assessment makes the assessment process more efficient and uses a simple, end-to-end process (Aichi, Bassiri, Benmokhtara & Belaaouad, 2020). This feature can be accessed easily using a smartphone to facilitate evaluation integrated with the web (Lai, Jong & Hasia, 2020;Rabiman, 2021;Wahyuningsih, Qohar & Satyananda, 2021;Wibowotomo, Rizal, Akbar & Kurniawan, 2021). The web was chosen as the integrator because the website has the advantage that it can be developed and updated according to needs (Sahidu, Gunawan, Indriaturrahmi & Astutik, 2017;Leksono, Marianingsih., Ilman & Maryani, 2021).…”
Section: Introductionmentioning
confidence: 99%